(untitled) (Advancements in Homeopathic Research, 2022)
Background: Cannabis use is rising and becoming a trending drug among youth. The drug is used in different forms, leading to intoxication, acute and long-term consequences. About 2.8% of Indians aged 10-75 years are current users of any cannabis product. Withdrawal from the drug use requires medical intervention and counselling. Objectives: To identify existing evidence in homoeopathy on drug deaddiction and cannabis use disorder and to update the physicians on diagnosis, risk behaviours, treatment and investigations associated with cannabis use disorder. Methods: A review of existing literature was conducted through internet sources and the CCRH headquarters library using keywords i.e. substance use, substance abuse, marijuana, cannabis abuse, drug abuse, cannabis use disorder etc. Data from studies reporting drug abuse to identify the type of drug use and homoeopathic treatment response in the withdrawal and long-term management and treatment of drug dependents was tabulated. Results: Although some studies have been conducted on drug withdrawal, no studies have been conducted on cannabis use disorder. More case studies and research on treatment of cannabis use disorder using Homoeopathy are needed. Interpretation: Physicians need to update themselves on diagnosis, risk behaviours, treatment and investigations to counter the condition and contribute to generating evidence-based literature on the homoeopathic approach for treating cannabis use disorder.